PENINGKATAN NILAI TAMBAH IKAN LELE MELALUI PENGOLAHAN KREATIF DAN BERKELANJUTAN DI DESA KALUKUBULA KECAMATAN SIGI BIROMARU KABUPATEN SIGI - Hartina, Hartina; Usman, Hasrudin; Padyawan, Andhy Rahmat; Syahril, Mohamad; Angriani, Ayu; Krismasari, Dian; Alfianti, Nur (Jurnal Abdi Insani, 2025)
Sigi Regency has significant potential in catfish cultivation, but most of its production is still sold fresh, resulting in low added value. Processing catfish, both meat and waste, into crackers with various flavors is a strategic innovation to increase economic value while reducing environmental pollution. Utilizing catfish waste, such as bones, skin, and heads, supports the principle of zero waste and creates environmentally friendly products. This activity aims to develop innovations in processing catfish meat and waste into high-value crackers, in order to increase community income and reduce environmental impact. The approach used is the Asset-Based Community Development (ABCD) community empowerment method through training in catfish cracker making. This process involves three types of products: catfish meat crackers, catfish waste crackers, and crackers made from a combination of catfish meat and waste. The activity stages include preparation, introduction to theory, and hands-on practice by the community of Kalukubula Village. This community service is carried out in Sigi Regency to increase the utilization of catfish, which has previously only been sold fresh. The activity focused on training in processing catfish meat and waste into crackers with original, spicy, and balado flavors. As a result, the community gained new skills in processing catfish creatively, efficiently, and environmentally friendly. The catfish cracker product is considered to have good market prospects and can create new business opportunities. This activity has proven to provide added value, strengthen the local economy, and support sustainability principles. This innovation is expected to become a model that can be replicated in other regions to support sustainable local economic development.